Power System & Short Circuit Analysis in PLTGU PLN UPDK Keramasan Using ETAP - Alisya, Karin; Pratama, Destra Andika; Anisah, Masayu (Universitas Negeri Padang, 2025)
This study aims to analyse the power flow and short circuit faults in the Gas and Steam Power Plant (PLTGU) of PT PLN Keramasan using ETAP software. Power flow analysis is carried out to determine the distribution of voltage, current, and power in the PLTGU electrical system and to ensure the efficiency and stability of system operations. The results of the power flow simulation show that the PT PLN Keramasan PLTGU can generate and distribute power with a stable voltage under various load conditions. In addition, short-circuit fault analysis aims to identify potential impacts. The short-circuit fault analysis finds important areas that are vulnerable to faults and require special protection. ETAP allows simulating various fault scenarios and establishing effective protection systems to reduce damage. This study emphasises the use of ETAP software as a powerful analytical tool in the planning and operation of the PLTGU electrical system. Power flow and short circuit analysis with ETAP is proven to improve the reliability, efficiency and safety of PT PLN Keramasan's PLTGU operations.